Allosteric inhibition of carnosinase (CN1) by inducing a conformational shift. (1st January 2017) - Peters, Verena; Schmitt, Claus P.; Weigand, Tim; Klingbeil, Kristina; Thiel, Christian; van den Berg, Antje; Calabrese, Vittorio; Nawroth, Peter; Fleming, Thomas; Forsberg, Elisabete; Wagner, Andreas H.; Hecker, Markus; et al.
Abstract: In humans, low serum carnosinase (CN1) activity protects patients with type 2 diabetes from diabetic nephropathy. We now characterized the interaction of thiol-containing compounds with CN1 cysteine residue at position 102, which is important for CN1 activity. Reduced glutathione (GSH), N-acetylcysteine and cysteine (3.2 ± 0.4, 2.0 ± 0.3, 1.6 ± 0.2 µmol/mg/h/mM; p < .05) lowered dose-dependently recombinant CN1 (rCN1) efficiency (5.2 ± 0.2 µmol/mg/h/mM) and normalized increased CN1 activity renal tissue samples of diabetic mice. Inhibition was allosteric. Substitution of rCN1 cysteine residues at position 102 (Mut1 C102S ) and 229 (Mut2 C229S ) revealed that only cysteine-102 is influenced by cysteinylation. Molecular dynamic simulation confirmed a conformational rearrangement of negatively charged residues surrounding the zinc ions causing a partial shift of the carnosine ammonium head and resulting in a less effective pose of the substrate within the catalytic cavity and decreased activity. Cysteine-compounds influence the dynamic behaviour of CN1 and therefore present a promising option for the treatment of diabetes.